Penerapan PSE (Pembelajaran Sosial Emosional) Dalam Mata Pelajaran Matematika Sebagai Upaya Menumbuhkan Fokus Belajar Siswa - Sri Armini, Ni Nengah; Hignasari, L.Virginayoga (Jayapangus Press, 2025)
Education is a broad area for students to develop talents, especially in enriching their competencies based on their interests. Based on this situation, the role of teachers is needed to be able to create an effective teaching and learning process to help students have optimal skills. The existence of the globalization era also provides a good opportunity for teachers to create the best learning atmosphere for students. The purpose of this study was to determine the effectiveness of PSE in helping students achieve well-being. This study uses a qualitative approach where the results of the effectiveness of PSE are obtained through data by conducting observation and interview activities with class VII J students at SMP Negeri 1 Bangli. The research data shows that students can learn mathematics with good focus after implementing PSE in learning activities. This can be supported through the implementation of Social Emotional Learning (PSE) which is able to stabilize students' Social and Emotional Competence (KSE). PSE is learning that focuses on optimizing the development of healthy character where students have healthy KSE. With healthy KSE which emphasizes the development of full awareness, students' learning focus on mathematics learning will increase.